ADMINISTRATION OF OMNI BIOTIC STRESS REPAIR IN CHILDREN'S AGE - Evgenia Barzashka; Teodora Valova (Peytchinski Publishing, 2022)
Background: In the last years of the old century and the beginning of the new century, the discovery that our gastrointestinal tract is home to a huge number of beneficial bacteria known as intestinal microflora changed the understanding of many physiological and pathological processes in the human body. Based on these scientific discoveries, the laboratories of the Allergozan Institute in Austria have created the synbiotic combinations "Omnibiotic", which are specific and aimed at specific problems related to human health. Purpose: The aim of the present study is to investigate the effect of the probiotic Omni Biotic Stress Repair in the treatment of functional abdominal pain (FAP) and some organic gastrointestinal diseases in childhood. Material and Methods: A prospective study has been done on children with FAP and PUD. For one year, we monitored 62 children with functional abdominal pain and duodenal ulcer who received Omni Biotic Stress Repair for 3 months. The causes of children's suffering were reported. Results: There are 39 children with functional abdominal pain, 22 of which are girls and 17 boys, and children with peptic ulcer disease - 23/12 boys and 11 girls/. The FAP group received Omni Biotic Stress Repair as self-therapy for three months. We reported very good results in all children. Only four children did not get the desired effect, and they dropped out of the study in the first month. In children with peptic ulcer disease, the probiotic Omni Biotic Stress Repair is added as a satellite therapy to the main treatment. When clinical remission occurred, the patients continued to take only probiotics for 3 months or more. Conclusions: Based on these scientific discoveries, the laboratories of the Allergozan Institute in Austria have created the synbiotic combinations "Omnibiotic", which are specific and aimed at specific problems related to human health.